2021
DOI: 10.4103/jfmpc.jfmpc_2223_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessing knowledge and practice about eye injuries first aid, with awareness about the importance of early management among general population in Asser Region, 2020

Abstract: Background: Eye injury is a leading cause of monocular blindness and is second only to cataract as the commonest cause of visual impairment. Injury is the commonest reason for eye-related emergency department visits. Aim: To assess population awareness regarding eye injuries first aids in Aseer region, Saudi Arabia. Methodology: A descriptive cross-sectional approach was used targeting all accessible population in Aseer region, Southern of Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 12 publications
4
24
4
Order By: Relevance
“…These high prevalence rates warrant research into community's level of knowledge of chemical eye injuries to reduce their incidence and complications. The analysis showed that the vast majority (95.1%) agreed that chemical injuries to the eye can cause ocular complications; a finding consistent with studies from Jeddah [ 9 ] (88.3%) and Aseer region (86.9%) [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These high prevalence rates warrant research into community's level of knowledge of chemical eye injuries to reduce their incidence and complications. The analysis showed that the vast majority (95.1%) agreed that chemical injuries to the eye can cause ocular complications; a finding consistent with studies from Jeddah [ 9 ] (88.3%) and Aseer region (86.9%) [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
“…The questionnaire was developed by the study authors based on previous research [ 9 , 10 ]. It included questions assessing demographic data (sex, age, job, education, and income) and questions assessing knowledge of ocular chemical burns and proper immediate steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted in three big cities Makkah, Jeddah, and Al-Taif. It shows that 23% of subjects have a history of eye injury, in contrast to other research done among the general population of Asser, which shows that a 15% of their participants have had a history of eye injuries [5]. Around three-quarters of our participants (73.7%) declined to rub their eyes to remove foreign objects.…”
Section: Discussioncontrasting
confidence: 74%
“…A closed-ended structured questionnaire was adapted from a study in the Asser region of Saudi Arabia [5].…”
Section: Data Collection Tools and Processmentioning
confidence: 99%